Introduction to Oracle Database 11g administration livelessons - McLaughlin, Michael; Safari eBooks ([S.l.] : Prentice Hall/Pearson, 2013)
"Michael McLaughlin teaches the basics of administering an Oracle database. Viewers will learn how to install the Oracle Database 11g software, work with SQL, understand how storage management works, manage users and security, manage schema objects, perform recovery and backup, and administer alerts, metrics, and advanced tuning. Throughout these LiveLessons, the DB console, which is the Oracle Enterprise Manager (OEM), is used to teach how to administer a database. By the end of these LiveLessons, viewers will be prepared to continue their studies on the path to becoming a DBA."--Resource description page.
Presenter, Michael McLaughlin.
Title from title screen.
Keywords: Oracle (Computer file); Database management; Relational databases; Electronic books